Early psychiatric referral after attempted suicide helps prevent suicide reattempts: A longitudinal national cohort study in South Korea - Kim, Hyewon; Kim, Yuwon; Shin, Myung-Hee; Park, Yoo-Jung; Park, Hyung-Eun; Fava, Maurizio; Mischoulon, David; Park, Mi Jin; Kim, Eun Ji; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
Introduction: Although people who attempted suicide tend to repeat suicide attempts, there is a lack of evidence on the association between psychiatric service factors and suicide reattempt among them. Methods: We used a nationwide, population-based medical records database of South Korea to investigate the use of psychiatric services before and after the index suicide attempt and the association between psychiatric service factors after the index suicide attempt with the risk of suicide reattempt. Results: Among 5,874 people who had attempted suicide, the all-cause mortality within three months after the suicide attempt was 11.6%. Among all suicide attempters, 30.6% had used psychiatric services within the six months before the suicide attempt; 43.7% had used psychiatric services within the three months after the suicide attempt. Among individuals who had visited clinics following attempted suicide, the cumulative incidence of suicide reattempt over a mean follow-up period of 5.1 years was 3.4%. About half of suicide reattempts occurred within one year after the index suicide attempt. Referral to psychiatric services within seven days was associated with a decreased risk of suicide reattempt (adjusted hazard ratio, 0.51; 95% confidence intervals, 0.29–0.89). Conclusions: An early psychiatric referral within one week after a suicide attempt was associated with a decreased risk of suicide reattempt.